Peranan Orangtua Dalam Mengantisipasi Kemerosotan Akhlak pada Anak Remaja - Siti Aminah (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2020)
This research is motivated by the number of students experiencing low morals. With this background, researchers are interested in examining whether there is an influence of the role of parents to overcome moral decline. The research was conducted at SMA Taman Islam, Cibungbulang District, Bogor Regency. The research population was 126 students while the sample was 30 students using purposive sampling technique. This study applies the correlation method with the research instrument using a questionnaire for the family environment and the value of report cards for PAI learning outcomes. The data were analyzed using the product moment correlation technique. The results of the study at the level of significance with the t-test showed tcount 1.84960> ttable 1.70113, this means that the influence of parental influence on students' morals is shown by KD (coefficient of determination) = 0.1089%, which means that the family environment contributes 10, 89% of the PAI learning outcomes of students.